POSSIBILITIES FOR A MORE FLUID RELATION BETWEEN SPORT PRACTICES AND CHILD SUBJECTIVITY. PRELIMINARY REFLECTIONS. (Fiep Bulletin - online, 2015)
The present study is a preliminary reflection that put together the results of two researches of which main objective was to understand the way the conception of childhood is conceived on the pedagogical system of ideas and methodologies of the sportive practices that compose the everyday of a social project, from the perspective of the actors that compose it. It also shows interpretative analysis on the role that the political discourses can play on the consolidation of the conceptions of subject and child subjectivity. The investigated context is a non-governmental social project pedagogically organized to attend children of urban periphery, which has as main line of its politic-pedagogical proposition the idea of Education and Health through Sport. The main instruments of the research were the analysis of documents, ethnographic observations and semi-structured interview. The analytical process showed that the influence of meritocratic ideologies for long rooted on the North-American liberal way of thinking is strongly present in those environments (governmental and non-governmental) pedagogically organized to “educate” the childhood from sport. The equal opportunity called “social inclusion” is understood as the act of situating all children in a same starting point and facilitate their individual courses inside the system without having to worry about politic and actions that modify their individual and collective differences, since every one of them will get from there, by their own efforts, where they deserve.
Keywords: Child subjectivity; Public discourses; Conception of sport.